Variation in phytoplankton community in Ninh Thuan - Binh Thuan coastal waters between post el niño year and enso neutral year - Ngoc Duyen, Huynh Thi; Luom, Phan Tuan; Le Van, Tran Thi; Mai Anh, Nguyen Thi; Minh Hue, Tran Thi; Lam, Nguyen Ngoc; Hai, Doan Nhu (Academia Journal of Biology, 2018)
Impacts of El Niño Southern Oscillation (ENSO) on the phytoplankton community have been studied in many different waters in the world. However, these effects on phytoplankton communities in coastal upwelling waters are still in need in various aspects such as specific responses of phytoplankton and its dynamics. Phytoplankton data of 15 stations in Ninh Thuan - Binh Thuan coastal area collected in July 2016 (post El Niño year) and July 2017 (ENSO neutral year) was analyzed and comparing using diversity indices, composition and density of the phytoplankton to measure influences of ENSO on the phytoplankton community structure in coastal upwelling of South Centre Viet Nam. The results revealed significant differences of average species number, the Margalef, Shannon, and Simpson diversity indices and the density of phytoplankton between the two years. These values and indices were significant higher in ENSO neutral year (2017) than the post El Niño year (2016), except the Pielou evenness index. Phytoplankton community structures of two periods were different by 82.26% based on SIMPER analyzing.